2014
DOI: 10.1111/jce.12575
|View full text |Cite
|
Sign up to set email alerts
|

The Transesophageal Echo Probe May Contribute to Esophageal Injury After Catheter Ablation for Paroxysmal Atrial Fibrillation Under General Anesthesia: A Preliminary Observation

Abstract: Esophageal lesions were seen in 30% of patients undergoing PVI alone under GA with use of TEE and in a similar proportion (22%) of patients undergoing TEE in the absence of left atrial ablation. This study makes the preliminary observation that one must be cognizant of the TEE probe as a potential contributor to esophageal injury after AF ablation. Larger studies are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…When we systematically screened patients who were undergoing TEE under general anesthesia for indications other than AF ablation (for example, cardioversion) using esophageal capsule endoscopy, we found a high incidence of asymptomatic esophageal injury (22%) in the form of erythema, abrasions, mucosal tears, or hematoma. 3 It is notable that the TEE probe was left in situ for the duration of the procedure performed under general anesthesia in the present report, which is similar to the scenario reported in our 3 patients previously. 2 It appears that probe retention for the duration of the procedure may also play a significant role in esophageal injury.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…When we systematically screened patients who were undergoing TEE under general anesthesia for indications other than AF ablation (for example, cardioversion) using esophageal capsule endoscopy, we found a high incidence of asymptomatic esophageal injury (22%) in the form of erythema, abrasions, mucosal tears, or hematoma. 3 It is notable that the TEE probe was left in situ for the duration of the procedure performed under general anesthesia in the present report, which is similar to the scenario reported in our 3 patients previously. 2 It appears that probe retention for the duration of the procedure may also play a significant role in esophageal injury.…”
supporting
confidence: 81%
“…Furthermore, when AF ablation was performed in the absence of TEE, we found no evidence of asymptomatic esophageal lesions with routine esophageal surveillance using esophageal capsule endoscopy. 3 A further point is that esophageal hematoma after AF ablation carries significant risk of morbidity from esophageal strictures, esophageal dysmotility, and residual odynophagia and vocal cord paralysis from extrinsic nerve compression. 2 Although the patient in the present report had complete radiographic resolution of the hematoma within 3 weeks, we have observed that symptoms may develop early (within days) or late (weeks thereafter) even after radiographic resolution of the hematoma and may persist for up to 12 months, as was seen in 1 patient in our series.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…18) Interestingly, Kumar, et al found that the transesophageal echo probe may also lead to an increase in esophageal damage. 5) After analyzing the patients with esophageal injury, we found no significant differences in patients without lesions due to the low incidence of EDEL. However a lower BMI was been shown to be a predictor for the development of esophageal injury.…”
Section: Discussionmentioning
confidence: 74%
“…The incidence ranged between 0% to almost 50%. [5][6][7][8] Zellerhoff, et al showed a structural change of the esophagus in 56% of the patients after PVI by endosonography. 9) To prevent esophageal complications, different approaches are being employed.…”
mentioning
confidence: 99%